Domestic violence sourcebook : basic consumer information about intimate partner abuse, stalking, sexual harassment, and human trafficking, including facts about risk factors, warning signs, and forms of physical, sexual, mental, emotional, and financial abuse in women, men, adolescents, recent immigrants, elders, and other specific populations ; along with facts about victims and abusers, strategies for preventing and intervening in abusive situations, guidelines for managing emergencies and making safety plans, interventions through workplaces and faith communities, tips regarding legal protections, a glossary of related terms, and a directory of resources for further information. - Omnigraphics, Inc. (Detroit, MI : Omnigraphics, Inc., 2016)
"Provides basic consumer health information on domestic violence. It describes the many forms of physical and emotional abuse, and discusses the physical, mental, and social effects of violence against intimate partners, children, teens, the elderly, immigrants, and other populations; gives strategies for prevention and intervention. Includes index, glossary of related terms and directory of resources"--
Includes bibliographical references and index.
Keywords: Family violence -- United States; Victims of family violence -- Services for -- United States; Sexual abuse victims -- Services for -- United States